2017
DOI: 10.1667/rr14518.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery Alters the Endothelial Surface Proteome: Externalized Intracellular Molecules as Potential Vascular Targets in Irradiated Brain Arteriovenous Malformations

Abstract: Stereotactic radiosurgery (SRS) is an established treatment for brain arteriovenous malformations (AVMs) that drives blood vessel closure through cellular proliferation, thrombosis and fibrosis, but is limited by a delay to occlusion of 2-3 years and a maximum treatable size of 3 cm. In this current study we used SRS as a priming tool to elicit novel protein expression on the endothelium of irradiated AVM vessels, and these proteins were then targeted with prothrombotic conjugates to induce rapid thrombosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 58 publications
4
28
0
Order By: Relevance
“…Accordingly, the smaller nidal vessels will receive a much greater radiation dose compared with the larger perinidal vessels. Such a proposed explanation is further supported by the findings of other researchers 22,42,47 who reported that, in contrast to the radiation-induced obliteration cascade of the smaller nidal vessels, the radiation-induced damage of the larger perinidal vessels will hinder the vessel wall nourishment and lead to subsequent increased vessel wall permeability.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Accordingly, the smaller nidal vessels will receive a much greater radiation dose compared with the larger perinidal vessels. Such a proposed explanation is further supported by the findings of other researchers 22,42,47 who reported that, in contrast to the radiation-induced obliteration cascade of the smaller nidal vessels, the radiation-induced damage of the larger perinidal vessels will hinder the vessel wall nourishment and lead to subsequent increased vessel wall permeability.…”
Section: Discussionsupporting
confidence: 60%
“…17,41 The thrombus formation is promoted by intimal injury, increased platelet aggregation, and turbulent blood flow that play an important role in the obliteration cascade of the small pathologic vessels of the AVM nidus. 35,41,42 Also, the subendothelial and the periadventitial proliferation and the contraction of the myofibroblasts, particularly the A phenotype, play an important role in shrinkage and eventual luminal closure of the thrombosed AVM after SRS. The replacement of the contracted thrombosed AVM by scar tissue is probably attributable to the proliferation of fibrocytes and V phenotype fibroblasts in the connective tissue stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of novel senescence-associated surface proteins may identify potential markers amenable to vascular targeting to treat or remove senescent cells as a therapeutic approach to treat age-associated disease [25-27]. Our own studies are investigating the use of radiation as a priming agent to induce novel marker expression for vascular targeting in brain arteriovenous malformations, of which radiation-induced senescence markers could be of use [51-53]. Identifying markers at the endothelial surface may have many applications for understanding and subsequently attenuating age-associated disease.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were analyzed using data-dependent and SWATH LC/MS/MS procedures described previously, with modifications [53, 69]. LC/MS/MS was performed using a TripleTOF 6600 mass spectrometer (AB SCIEX) equipped with a NanoLC™ 400 liquid chromatography system (Eksigent) and cHiPLC unit (Eksigent).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, we aim to use radiosurgery to prime the AVM endothelium to induce potential targets. Our previous studies demonstrated that radiation can induce upregulation of surface biomarkers on the AVM endothelium thus discriminating it from normal vessels [10][11][12][13][14]. These proteins may serve as potential targets for ligand-directed pro-thrombotic conjugates, enhancing the thrombotic response when induced with radiation.…”
Section: Introductionmentioning
confidence: 99%